The evolution of the agroturistic pensions in Buzau County, period 2004 - 2011 - Diana Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Unlike other counties, whose relief consists only of plains (Teleorman , Ialomiţa) , mountains or hills-(Braşov, Sibiu, etc.), Buzău county has plain, hill and mountain, what makes it distinctive from other counties. Buzău county region is one of the important areas in terms of tourist potential in its natural, historic, and effective architecture monuments, folk art, people living here, householders, good preservers of old traditions.In the County there is a fairly developed agroturistic network, supported mainly by ANTREC, most hostels are in the area Sarata Monteoru, and then in the Buzău Valley (Berca, Nehoiu, Gura Teghii, Siriu). Most tourists and agrotouristic pensions of Buzau County are small, indicating that they only bring complementary tourist income for their owners. There are few agrotouristic pensions deriving income from this activity only.
Keywords: 330; agritourism; accommodation; overnights; average rate